Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
x^2 +2x -6
Step-by-step explanation:
f(x)=2x+1
g(x)=x^2-7,
(f+g)(x) = 2x+1 + x^2 -7
Combine like terms
= x^2 +2x -6
f (x) = 2x + 1
g (x) = x² - 7
(f+g) (x) = 2x+1 + x² - 7
Adding like terms
⇛ x² + 2x - 6
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.